خصال الباحث الأخلاقيات ومواصفاته العقلية - سعودي كحول; حاج علي كمال (University Of Eloued جامعة الوادي, 2023)
The reality of scientific research in recent years reveals the crowding of Arab and non-Arab libraries with extensive intellectual production in all kinds of scientific knowledge and in the field of social sciences and humanities as well. Scientific plagiarism in the usual and unknown form, and here there are no ethical controls, and a violation of the scientific method, its methods and principles, as well as the lack of or weak knowledge of the principles, rules and conditions of scientific research, and to clarify the essence of the problem in question, with its sublime scientific and human dimensions, we address in our research paper these foundational aspects of the importance of scientific research And the academic in the correct sense and all the mental, scientific and ethical qualities and characteristics that move the researcher from the question about the object to the question about what it ought to be
The researcher's ethical characteristics and mental specifications
مداخلة
Keywords: البحث العلمي; السرقة العلمية; الأخلاق; الصفقات العقلية; Scientific research; scientific theft; morals; mental traits